Pathogenic Variants in ACTRT1 Cause Acephalic Spermatozoa Syndrome - Sha, Yanwei; Liu, Wensheng; Li, Lin; Serafimovski, Mario; Isachenko, Vladimir; Li, Youzhu; Chen, Jing; Zhao, Bangrong; Wang, Yifeng; Wei, Xiaoli (Frontiers in Cell and Developmental Biology, 2021)
Acephalic spermatozoa syndrome is a rare type of teratozoospermia, but its pathogenesis is largely unknown. Here, we performed whole-exome sequencing for 34 patients with acephalic spermatozoa syndrome and identified pathogenic variants in the X-linked gene, ACTRT1, in two patients. Sanger sequencing confirmed the pathogenic variants of ACTRT1 in the patients. Both pathogenic variants of ACTRT1 were highly conserved, and in silico analysis revealed that they were deleterious and rare. Actrt1-knockout mice exhibited a similar acephalic spermatozoa phenotype. Therefore, we speculated that mutations in ACTRT1 account for acephalic spermatozoa syndrome. Moreover, the patients in this study conceived their children through artificial insemination. This study provides further insights for clinicians and researchers regarding the genetic etiology and therapeutic strategies for acephalic spermatozoa patients with pathogenic variants in ACTRT1.